2021
DOI: 10.1037/cou0000440
|View full text |Cite
|
Sign up to set email alerts
|

Using computerized text analysis to examine associations between linguistic features and clients’ distress during psychotherapy.

Abstract: Raw linguistic data within psychotherapy sessions may provide important information about clients' progress and well-being. In the current study, computerized text analytic techniques were applied to examine whether linguistic features were associated with clients' experiences of distress within and between clients and whether changes in linguistic features were associated with changes in treatment outcome. Transcripts of 729 psychotherapy sessions from 58 clients treated by 52 therapists were analyzed. Prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
1
14
0
4
Order By: Relevance
“…Regardless, our findings suggest that individuals may need increasing support over time for their increasing negative emotion expression over time. Using more negative emotion words can increase feelings of distress immediately afterwards [ 86 , 87 , 88 ]. This could be especially problematic for weight management programs since negative emotion predicts emotional eating and reduced physical activity [ 20 , 65 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, our findings suggest that individuals may need increasing support over time for their increasing negative emotion expression over time. Using more negative emotion words can increase feelings of distress immediately afterwards [ 86 , 87 , 88 ]. This could be especially problematic for weight management programs since negative emotion predicts emotional eating and reduced physical activity [ 20 , 65 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast this study examined psychodynamic psychotherapy sessions in which speech is typically unbalanced, where clients usually speak more than therapists. For example, analyzing psychodynamic sessions, Shapira et al (2020) found that 78% of all session utterances were made by the clients and 22% by the therapists.…”
Section: The Vocal Channel In Psychotherapymentioning
confidence: 99%
“…By contrast this study examined psychodynamic psychotherapy sessions in which speech is typically unbalanced, where clients usually speak more than therapists. For example, analyzing psychodynamic sessions, Shapira et al (2020) found that 78% of all session utterances were made by the clients and 22% by the therapists. Hence, we opted to use the speech analysis method based on speech-turn switches proposed by Levitan and Hirschberg (2011) who found that vocal features surrounding turn-switches carry more information about the emotional interaction between speakers than do average vocal scores from entire speech turns.…”
Section: Intrapersonal Affect Dynamicsmentioning
confidence: 99%
“…Usage In one study conducted in our lab, we found correlations between a client's and therapist's positive/negative emotion words and client's and therapist's positive/negative emotions as reported in the POMS questionnaire. In another study, that uses our positive-negative emotion lexicons, Shapira et al (2020) examined the relationship between the number of emotion words spoken in a session and the client's self-reported questionnaire regarding her well-being. The findings are consistent with the literature and in line with theoretical views highlighting the role of positive emotions and negative emotions and the association to well-being (e.g., Blatt (1995); Shahar et al (2020); Morales et al (2017)).…”
Section: Valence (Positive and Negative)mentioning
confidence: 99%